Association between lifestyle, multiple chronic conditions, mental health status and the severity of lower urinary tract symptoms/benign prostatic hyperplasia in Chinese elderly - Wu, Yifan; Zhang, Yuwei; Liu, Xinwei; Huang, Yongneng; Hua, Ye; Feng, Ninghan (Frontiers in Medicine, 2025)
Background and objectiveThe etiology and pathogenesis of lower urinary tract symptoms/benign prostatic hyperplasia (LUTS/BPH) are complex, and understanding of factors related to symptom severity can improve the disease prognosis. The aim of this study was to explore the association between LUTS/BPH severity and lifestyle, multiple chronic conditions (MCC), and mental health status in Chinese elderly individuals, and to provide a reference for developing comprehensive intervention measures.MethodsA total of 806 patients aged 60 and above with LUTS/BPH were divided into mild and moderate-to-severe groups based on IPSS assessment. All participants completed data collection on general demographics, clinical characteristics, lifestyle factors, MCC, and mental health status (including anxiety, depression, and sleep quality). A binary logistic model was employed to investigate the influence of lifestyle, MCC, and mental health status on LUTS/BPH severity.ResultsThe moderate-to-severe group had significantly higher rates of unhealthy lifestyle habits, MCC, and mental health problems compared to the mild group. After adjusting for confounders (such as age, disease duration, prostate volume, total prostate-specific antigen, C-reactive protein, post-voided residual urine, urea nitrogen, etc.), current smoking (OR = 1.995, 95%CI:1.270–3.134), unhealthy dietary habits (OR = 1.590, 95%CI: 1.059–2.386), and lack of active exercise (OR = 1.996, 95%CI:1.274–3.127) were positively correlated with the severity of BPH/LUTS. Conversely, the absence of heart disease (OR = 0.435, 95%CI:0.268–0.707), normal lipid profile (OR = 0.587, 95%CI:0.354–0.973), no diabetes mellitus (OR = 0.523, 95%CI:0.312–0.878), no depressive disorder (OR = 0.447, 95%CI:0.204–0.979) and no sleep disorder (OR = 0.494, 95%CI:0.322–0.758) were significantly negatively correlated with the severity of BPH/LUTS.ConclusionThe study revealed a strong correlation between the severity of LUTS/BPH and poor lifestyle, multiple chronic diseases, and mental health problems. Therefore, the prevention and treatment of LUTS/BPH should fully consider these factors.